Educational Supervision as a Catalyst for the Internal Quality Assurance in Secondary Schools - Odefunsho, Amos Olukayode; Odefunsho, Amos Olukayode; Ayoku, O.B. (International Journal of Educational Management, 2022)
This paper focuses on Educational Supervision as a catalyst for the Internal Quality Assurance highlighting the concepts of Education, Supervision and Educational Supervision, differences between Supervision and Inspection, Purpose of Educational Supervision, Quality Assurance and Total Quality Management (TQM) as well as Quality in Teaching and Learning. Also, Educational Supervision as a viable tool for quality output in schools be it Primary, Secondary and Tertiary education and the Techniques of Supervision were discussed like classroom observation, teacher visitation, demonstration, workshop, micro-teaching, listening to recordings, guided practice and research. Since haphazard unsupervised instruction may disrupt the standard of education, it is therefore suggested that Principals as catalysts should facilitate the implementation of the various sets of Educational Supervision activities that will improve the teaching-learning situation in the input-process-output framework. This is geared towards an effective, viable, vibrant and qualitative educational system.